Policy analysis of sustainable traditional market management - Utari, Retno; Soesilo, Tri Edhi Budhi; Agustina, Haruki (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: SNI People's Market is a national standard in the construction and management of trade facilities. The Healthy Market implementation policy serves to regulate the health of the market environment. The policy of implementing SNI for People's Market and the policy of organizing Healthy Market are expected to be the guidelines in managing people's market. However, in reality, not all public markets in DKI Jakarta implement the two policies. The purpose of the research is to analyze the condition of public markets in Perumda Pasar Jaya in terms of SNI criteria for Public Markets and Healthy Markets, and analyze the implementation of SNI for Public Markets and Healthy Markets and based on the assessment of the central government and local government. Methods: The research method used is a combination of quantitative and qualitative methods using a qualitative approach that combines descriptive statistics and a comparison matrix. Results: The research results based on field observations show that the condition of public markets in Perumda Pasar Jaya has limitations in the provision of facilities that are a requirement in the implementation of SNI for Public Markets and Healthy Markets. In addition, the implementation of SNI People's Market and Healthy Market has obstacles in its implementation from the point of view of the central government and local government.